Dynapenia is associated with a higher risk of depressive symptoms among older adults - Chang, Chih-Ching; Liao, Yung; Chen, Jiaren; Lai, Ting-Fu; Hsueh, Ming-Chun; Park, Jong-Hwan; Chang, Yen-Jung (Frontiers in Public Health, 2025)
BackgroundDepression affects the global burden of disability among older adults. Although dynapenia is related to disability and potential psychological health outcomes, its association with depressive symptoms remains uncertain. Accordingly, the objective of the current study was to investigate this association in older Taiwanese adults, applying the 2019 Asian Working Group for Sarcopenia (AWGS) classification of dynapenia.MethodsOur research utilized a cross-sectional design implemented from September 2020 to December 2021, enrolling older adults aged over 65 years through National Taiwan University Hospital. The participants underwent standard assessments, including handgrip dynamometry for muscle strength, bioelectrical impedance analysis for muscle mass, and a 6-meter walk test for physical performance, to confirm the classification of dynapenia. The 15-item Geriatric Depression Scale (GDS-15) served as the tool to evaluate whether participants were at risk of potential depressive symptoms. The correlation between dynapenia and the risk of geriatric depressive symptoms was assessed through unadjusted and adjusted binary logistic regression analyses.ResultsIn total, 197 older adults (mean age was 80.5 ± 7.0 years; 52.8% female; 17.3% at risk of depressive symptoms; 55.8% with dynapenia) were included. Regardless of the different models, dynapenia remained significantly and positively related to the risk of geriatric depressive symptoms (OR [odds ratio]: 2.67; 95% CI [confidence interval]: 1.01–7.05; p = 0.048) after adjusting for potential confounders.ConclusionOur findings highlighted a significant association between dynapenia, as classified by the 2019 AWGS criteria, and a higher risk of depressive symptoms in older Taiwanese adults. Public health professionals and practitioners should screen individuals with dynapenia for depressive symptoms to facilitate the early detection of depression. Future research should investigate the complex physiological and psychological mechanisms underlying this association.